2006
DOI: 10.4049/jimmunol.176.7.3890
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Enhanced Pulmonary Clearance of Pseudomonas aeruginosa by Muc1 Knockout Mice

Abstract: MUC1 (MUC1 in human and Muc1 in nonhumans) is a membrane-tethered mucin that interacts with Pseudomonas aeruginosa (PA) through flagellin. In this study, we compared PA pulmonary clearance and proinflammatory responses by Muc1−/− mice with Muc1+/+ littermates following intranasal instillation of PA or flagellin. Compared with Muc1+/+ mice, Muc1−/− mice showed increased PA clearance, greater airway recruitment of neutrophils, higher levels of TNF-α and KC in bronchoalveolar lavage fluid, higher levels of TNF-α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
151
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 126 publications
(160 citation statements)
references
References 30 publications
9
151
0
Order By: Relevance
“…A similar biphasic response was previously reported when evaluating TNF-a production induced by the same flagellin concentrations in mouse alveolar macrophages. 34 As flagellin monomers can polymerize in solution under certain conditions, reconstituting flagellar fibers undistinguishable from native flagella, 35 it is possible that increasing FliC concentrations tend to more easily re-aggregate, reducing the ability of FliC preparation to prevent neutrophil apoptosis. On the other hand, it has been previously shown that flagellin induces self-tolerance by blocking the release of IRAK from the TLR5 complex in flagellin-tolerant cells.…”
Section: Discussionmentioning
confidence: 99%
“…A similar biphasic response was previously reported when evaluating TNF-a production induced by the same flagellin concentrations in mouse alveolar macrophages. 34 As flagellin monomers can polymerize in solution under certain conditions, reconstituting flagellar fibers undistinguishable from native flagella, 35 it is possible that increasing FliC concentrations tend to more easily re-aggregate, reducing the ability of FliC preparation to prevent neutrophil apoptosis. On the other hand, it has been previously shown that flagellin induces self-tolerance by blocking the release of IRAK from the TLR5 complex in flagellin-tolerant cells.…”
Section: Discussionmentioning
confidence: 99%
“…The PA infection and assessment of lung bacterial clearance were performed as we described previously [35]. Briefly, PA strain PA01…”
Section: Pa Infectionmentioning
confidence: 99%
“…Stimulated AMs, secreting a number of pro-inflammatory cytokines and chemokines, play a direct role in the recruitment of neutrophils [26,34].…”
Section: Airway Inflammation and Infectionmentioning
confidence: 99%